Myanmar's Rohingya genocide - Lee, Ronan 1976- (London)
xi, 306 sayfa
Keywords: “The genocide in Myanmar has drawn global attention as Nobel Peace Prize laureate Aung San Suu Kyi appears to be presiding over human rights violations, forced migrations and extra-judicial killings on an enormous scale. This unique study draws on thousands of hours of interviews and testimony from the Rohingya themselves to assess and outline the full scale of the disaster. Casting new light on Rohingya identity, history and culture, this will be an essential contribution to the study of the Rohingya people and to the study of the early stages of genocide. This book adds convincingly to the body of evidence that the government of Myanmar has enabled a genocide in Rakhine State and the surrounding areas“ --